The Deferred Action for Childhood Arrivals program and birth outcomes in California: a quasi-experimental study - Jacqueline M. Torres; Emanuel Alcala; Amber Shaver; Daniel F. Collin; Linda S. Franck; Anu Manchikanti Gomez; Deborah Karasek; Nichole Nidey; Michael Hotard; Rita Hamad; Tania Pacheco-Werner (BMC, 2022)
Abstract Background The Deferred Action for Childhood Arrivals (DACA) program provides temporary relief from deportation and work permits for previously undocumented immigrants who arrived as children. DACA faced direct threats under the Trump administration. There is select evidence of the short-term impacts of DACA on population health, including on birth outcomes, but limited understanding of the long-term impacts. Methods We evaluated the association between DACA program and birth outcomes using California birth certificate data (2009-2018) and a difference-in-differences approach to compare post-DACA birth outcomes for likely DACA-eligible mothers to birth outcomes for demographically similar DACA-ineligible mothers. We also separately compared birth outcomes by DACA eligibility status in the first 3 years after DACA passage (2012-2015) and in the subsequent 3 years (2015-2018) - a period characterized by direct threats to the DACA program - as compared to outcomes in the years prior to DACA passage. Results In the 7 years after its passage, DACA was associated with a lower risk of small-for-gestational age (− 0.018, 95% CI: − 0.035, − 0.002) and greater birthweight (45.8 g, 95% CI: 11.9, 79.7) for births to Mexican-origin individuals that were billed to Medicaid. Estimates were consistent but of smaller magnitude for other subgroups. Associations between DACA and birth outcomes were attenuated to the null in the period that began with the announcement of the Trump U.S. Presidential campaign (2015-2018), although confidence intervals overlapped with estimates from the immediate post-DACA period. Conclusions These findings suggest weak to modest initial benefits of DACA for select birthweight outcomes during the period immediately following DACA passage for Mexican-born individuals whose births were billed to Medicaid; any benefits were subsequently attenuated to the null. The benefits of DACA for population health may not have been sufficient to counteract the impacts of threats to the program's future and heightened immigration enforcement occurring in parallel over time.